Isolation and Antimicrobial Resistance of Escherichia coli and Salmonella enterica subsp. enterica (O:6,8) in Broiler Chickens - Bezerra, Windleyanne Gonçalves Amorim; Silva, Isaac Neto Goes da; Vasconcelos, Ruben Horn; Machado, Débora Nishi; Lopes, Elisângela de Souza; Lima, Suzan Vitória Girão; Teixeira, Régis Siqueira de Castro; Lima, Jéssica Bezerra; Oliveira, Felipe Rebouças; Maciel, William Cardoso (Acta Scientiae Veterinariae, 2016)
Background: The third largest poultry flock in Northeast Brazil is located in Ceará State. Some pathogens are commonly disseminated in broiler chicken flocks, such as the bacteria from the Enterobacteriaceae family. Among these, some strains of Escherichia coli are frequently associated with different pathological manifestations in domestic animals, while bacteria from the genus Salmonella are considered the most frequent enteric pathogens reported causing foodborne infections in humans. Therefore, this study aimed to evaluate the prevalence and antimicrobial resistance of Salmonella sp. and Escherichia coli strains isolated from broiler chickens in the Metropolitan Region of Fortaleza city, Brazil. Materials, Methods & Results: Samples were collected from July-2014 to March-2015 in ten broiler chicken farms located in the Metropolitan Region of Fortaleza city, Brazil, with birds in pre-slaughter age. From each farm, 100 individual cloacal swabs were randomly collected from broilers independent of clinical status. Distinct methodologies were used in order to provide optimal isolation conditions for both the bacterial species. For Escherichia coli, the methodology consisted in enrichment with BHI broth, plating in EMB agar and biochemical identification, after which some isolates were maintained in nutrient agar for antimicrobial resistance evaluation. For the isolation of Salmonella sp., a standard method was used with pre-enrichment, selective enrichment, selective plating and biochemical identification steps. Antimicrobial susceptibility test (AST) was performed with disk diffusion technique and the following antibiotics were tested: ampicillin, ceftiofur, ciprofloxacin, trimethoprim-sulfamethoxazole, polymyxin B, gentamycin, cloranfenicol, tetracycline, azithromycin and fosfomycin. According to the methodology used, 95.9% of samples were positive for Escherichia coli and the most frequent resistance was to trimethoprim-sulfamethoxazole. Salmonella sp. was isolated from 0.2% of the samples, which were identified as the serotype Salmonella enterica subsp. enterica O:6,8. Both isolates presented the same antimicrobial resistance profile, which were resistant to six, out of ten tested antibiotics (trimethoprim-sulfamethoxazole, tetracycline, ciprofloxacin, azithromycin, chloramphenicol and ceftiofur). Discussion: The low prevalence of Salmonella observed in this study have also been reported by other studies performed in poultry farms in Ceará State, which suggests a good status for this pathogen in the local industry, however further efforts in order to eradicate this pathogen must be applied. The salmonella serotype detected in this study is rarely reported in the literature, especially from the poultry industry. In Brazil, the use of tetracyclines, quinolones and penicillins as feed additives or growth promoters is prohibited; however, a high resistance to drugs from these groups was detected. In addition, multidrug resistant E. coli isolates presented more elevated rates than other studies reported in the literature with antibiotics commonly used in the poultry industry and this may indicate an excessive use of these drugs in the production routine. These results should serve as a warning for surveillance programs to evaluate the incidence of these microorganisms as well as their antimicrobial resistance rates, which may be an important tool for control and prevention in meat poultry production.